2018
DOI: 10.3892/ol.2018.9745
|View full text |Cite
|
Sign up to set email alerts
|

miR‑200b and miR‑200c co‑contribute to the cisplatin sensitivity of ovarian cancer cells by targeting DNA methyltransferases

Abstract: Cisplatin is a first-line chemotherapy drug that is commonly used in the treatment of epithelial ovarian cancer (EOC). However, insensitivity to cisplatin markedly influences the outcomes of chemotherapy. MicroRNAs (miRNAs/miRs) have been demonstrated to modulate drug resistance in a number of types of cancer. The aim of the present study was to investigate the key miRNAs involved in modulating drug resistance in ovarian cancer cells. miR-200b and miR-200c were identified to be frequently deregulated in ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Moreover, the higher expression of miR-200c was exclusively associated with carcinoma at the advanced stages [128]. A study carried out by Liu and colleagues claimed that enhancing the expression of miR-200b and miR-200c could lead to apoptosis in EOC [129]. Results from this study indicated that miR-200b and miR-200c control the downregulation of DNA methyltransferase (DNMTs) and increase chemotherapeutic sensitivity in ovarian cancer cells leading to better drug efficacy and tumor suppression.…”
Section: Indirect Cellular Processes That Affect Apoptosis Inductionmentioning
confidence: 99%
“…Moreover, the higher expression of miR-200c was exclusively associated with carcinoma at the advanced stages [128]. A study carried out by Liu and colleagues claimed that enhancing the expression of miR-200b and miR-200c could lead to apoptosis in EOC [129]. Results from this study indicated that miR-200b and miR-200c control the downregulation of DNA methyltransferase (DNMTs) and increase chemotherapeutic sensitivity in ovarian cancer cells leading to better drug efficacy and tumor suppression.…”
Section: Indirect Cellular Processes That Affect Apoptosis Inductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are a group of these key molecules that have been investigated in various types of cancer (9,10). These small RNAs have no capacity of protein coding, but exert regulatory roles in gene expression at the post-transcriptional level (11). In addition, miRNAs are involved in the regulation of various cell processes, such as cell proliferation, migration, invasion, differentiation, cell cycle and apoptosis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT3A was reported as the direct target of cisplatin-sensitizing miR-200b and miR-200c in A2780/CDDP cells (J. Liu et al, 2019); however, our study first confirmed DNMT3A as a promoter of cisplatin resistance with cell models. And we first identified that DNMT3A antagonized the cisplatin-sensitizing effect of miR-143 in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 42%